Application of a central iliac arteriovenous coupler device in severe treatment-resistant hypertension: a 3.5-year follow-up. Issue 12 (December 2018) - Jung, Susanne; Ott, Christian; Karg, Marina V.; Bosch, Agnes; Schmid, Michael; Schlundt, Christian; Achenbach, Stephan; Schmieder, Roland E.
Abstract : Objective: In patients with resistant hypertension, percutaneous placement of an iliac arteriovenous coupler device leads to a reduction of blood pressure (BP) via decreased total vascular resistance and improved arterial compliance. However, long-term efficacy and safety need to be further explored. We report on the first case of 3.5-year follow-up in a patient who underwent implantation of an iliac arteriovenous coupler device. Results: A patient with resistant hypertension was admitted to hospital. Despite treatment with six anti-hypertensive drugs, his BP was poorly controlled. Previously, he had undergone renal denervation, which did not cause a significant BP decrease. Therefore, an arteriovenous coupler device was implanted, leading to an immediate and significant BP decrease. The patient was discharged with an office BP of 122/71 mmHg. After 3 months, there was a sustained BP decrease (−14/9 mmHg), whereas later, it was fluctuant (office BP: 147–173/85–95 mmHg, ABPM: 153–166/81–94 mmHg) probably due to medication non-adherence confirmed by a urinary toxicological screening test. Follow-up right heart catheterization showed changes in hemodynamic parameters related to volume congestion, which were accompanied by progressive dyspnea and weight gain. This was controlled by an optimized diuretic therapy. Additionally, an invasive closure maneuver was performed, leading to an immediate BP increase after closure and a similar decrease after re-opening of the anastomosis, verifying its proper long-term function. Conclusion: The implantation of an iliac arteriovenous coupler device appears to be a promising and effective method to decrease BP and therefore reduce cardiovascular risk in patients with severe, treatment-resistant hypertension.